2008
DOI: 10.1111/j.1601-0825.2007.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of intra‐oral ultrasonography to predict neck metastasis in patients with tongue carcinoma

Abstract: High-quality ultrasonic images were obtained, and all lesions over 1 mm thickness by histology were detected. There was a significant correlation (P < 0.0001) between measurements of tumor thickness by US and histology. Univariate analysis showed that the histological parameters influencing neck metastasis were mode of invasion (P = 0.0006), muscular invasion (P < 0.0001), stromal reaction (P = 0.0002), and tumor thickness (P = 0.0004). Of the ultrasonographic parameters, shape of margin (P = 0.019), pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 49 publications
1
47
0
1
Order By: Relevance
“…3,[6][7][8][9][10] This methodology has also been useful for inspecting inflammation and tumours around the tonsils. 11 Kutluhan et al 12 reported that the pre-operative measurement of lesions for tonsillectomy by IOUS was reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[6][7][8][9][10] This methodology has also been useful for inspecting inflammation and tumours around the tonsils. 11 Kutluhan et al 12 reported that the pre-operative measurement of lesions for tonsillectomy by IOUS was reliable.…”
Section: Discussionmentioning
confidence: 99%
“…2 On the other hand, in case of intraoral ultrasonography (IOUS), we can place a probe above the lesion with confirmation of its position and can observe its sonographic characteristics at the same time. In the article of Natori et al, 3 which evaluated the detection of tongue carcinoma, all lesions over 1 mm in tumour thickness on histological section were detectable on IOUS images using a 7.5-MHz linear probe.…”
Section: Introductionmentioning
confidence: 99%
“…Such diagnostic also included two reports about ultrasound, but we had to discard studies of ultrasonography, as these are focused on the detection of cervical metastases 31 or the determination of lingual tumour density at stages T1 and T2. 32 Although methods such as CT, MRI, panoramic radiography and CBCT have a high capacity for detection of mandibular bone tissue invasion in patients, we found a large variation between minimum and maximum sensitivity values.…”
Section: Discussionmentioning
confidence: 99%
“…CT and MRI have a number of limitations related to the evaluation of the precise size and extent of the tumor, small lesions or the presence of metal artifacts can be confounding factors [10]. A histopathological examination following a biopsy is useful, not only for confirming the diagnosis but also for estimating the malignant potential of the lesion; however, grading tumor invasion accurately from a biopsy is difficult because only a limited part of the tumor tissue is sampled [5]. Ultrasonography is a noninvasive, rapid, easily repeatable, and inexpensive examination.…”
Section: Introductionmentioning
confidence: 99%
“…However, SCC of the oral cavity has an even worse prognosis when associated with metastatic cervical nodes [4]. Therefore, the metastatic potential of tongue carcinoma should be graded preoperatively to help determine the requirement for neck dissection [5].…”
Section: Introductionmentioning
confidence: 99%